Low concentrations of Lactobacillus rhamnosus GG (Yoba(®)) are safe in male Drosophila melanogaster - Kasozi, Keneth Iceland (BMC Res Notes, 2019)
OBJECTIVE: The purpose of the study was to generate information on the safety of probiotics, thus the study objectives were to evaluate the effects of Yoba(®) on basic physiochemical properties. The study assessed male w(1118) Drosophila melanogaster which were provided food supplemented with Yoba(®) at 1%, 3%, 6%, and 12% on motor function, total protein, catalase activity, and hydrogen peroxide scavenging activity and lifespan. RESULTS: Yoba(®) at high concentration (≥ 6%) increased locomotor activity in Drosophila melanogaster, however, total protein, catalase, and hydrogen peroxide scavenging activity were significantly higher at 1% Yoba(®) compared to 3%, 6%, and 12% Yoba(®). Yoba consumed at 1% was associated with greater physiological benefits in Drosophila melanogaster. Findings in the study offer a rationale for the consumption of Yoba(®) at 1% in humans as is currently being promoted by the Yoba for Life consortium, however, high concentrations of Yoba(®) would disrupt physiological function as shown by this study.